The Role of Corporate Social Responsibility in Advance Human Rights in The Business Sector - Selvina Khomairoh; Mohamad Nur Efendi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
Corporate Social Responsibility (CSR) is vital in advancing human rights in the business sector, especially in the increasingly complex globalization and technology era. This study examines CSR's role in protecting and promoting human rights through a comprehensive literature review. The method used is literature analysis, which includes empirical studies, reports, and academic publications related to CSR implementation and its impact on human rights. The findings show that CSR can be an important mechanism to improve corporate transparency, accountability, and compliance with human rights standards. Effective CSR initiatives often involve protecting workers' rights, non-discrimination policies, and ethical supply chain management. In addition, good CSR practices can also help companies manage reputational risk and strengthen stakeholder relationships. However, this study also identified significant challenges, including the lack of consistent regulation and the risk of greenwashing where companies claim commitment to CSR without real action. The implications of these findings emphasize the importance of a holistic and sustainable approach to CSR implementation, as well as the need for stricter regulation and greater awareness of consumers and society towards corporate social responsibility. This study suggests further research to explore more effective ways of leveraging CSR to advance human rights across different industrial and geographic contexts.